2004
DOI: 10.1192/bjp.185.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of severe acute respiratory syndrome on health workers in a tertiary hospital

Abstract: The outbreak of SARS could be regarded as an acute episode of a bio-disaster, leading to a significantly high rate of psychiatric morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
675
10
29

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(796 citation statements)
references
References 18 publications
51
675
10
29
Order By: Relevance
“…However, once the SARS epidemic was under control (around July, 2003), this study found that only 17.3% of the health care workers had developed mental symptoms. This ratio was far lower than that reported by Chong et al [6] (with participants also coming from southern Taiwan), who mentioned that 75.3% of subjects appeared to have mental health problems during the SARS outbreak (from May to June, 2003). This study also showed that the mental symptoms of the majority of participants obviously lessened, little by little, several months after the SARS epidemic was under control.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, once the SARS epidemic was under control (around July, 2003), this study found that only 17.3% of the health care workers had developed mental symptoms. This ratio was far lower than that reported by Chong et al [6] (with participants also coming from southern Taiwan), who mentioned that 75.3% of subjects appeared to have mental health problems during the SARS outbreak (from May to June, 2003). This study also showed that the mental symptoms of the majority of participants obviously lessened, little by little, several months after the SARS epidemic was under control.…”
Section: Discussioncontrasting
confidence: 52%
“…In Taiwan, an investigation of 1,257 health care workers showed that more than 3/4 of the participants felt that their job put them at great risk of exposure to SARS, and therefore worked with a substantial burden. The prevalence of psychiatric morbidity was as high as 75.3%, which was three times that of the general population [6]. …”
Section: Introductionmentioning
confidence: 99%
“…In the review of previous studies, the prevalence of psychological morbidity in nurses was about 18 to 48.8% 12,[29][30][31][32] ; only one report, from Nigeria, showed lower psychological morbidity rates than our nurse group. The higher morbidity rates among nurses reported in other surveys 13,15,29) may be due to specific work situations or due to different methodology in cutoff points of the GHQ. Therefore, this is a study involving healthcare workers, the gender differences in psychological morbidity usually found between the sexes may disappear as a result of the type of work they do.…”
Section: Discussionmentioning
confidence: 74%
“…There are few epidemiological studies on the quality of life of health care workers in hospitals, where certain stressors influencing quality of life can be found. These stressors included low autonomy, limited involvement in decision-making, noisy and hot environments, heavy physical load, long work hours, work shifts, exposure to toxins and infectious agents or patients [10][11][12][13][14] . Situations pertaining to the physical workload, death of a patient, and communication problems with physicians and nursing administrators have been ranked most highly stressful 15) .…”
mentioning
confidence: 99%
“…Earlier reports have also shown mixed attitudes among healthcare workers toward coping with infectious diseases. For example, during the SARS epidemic, 79% of Taiwanese healthcare workers perceived fear and 37% reported they would accept the risk 22) . Such perceptions may reflect the level of threat perceived by the responders at that time.…”
Section: Discussionmentioning
confidence: 99%